1983
DOI: 10.2307/1942532
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Selection Attributes of an Avian Community: A Discriminant Analysis Investigation

Abstract: Habitat use characteristics of all bird species occurring in the lower Colorado River valley were studied. Seventy—two transects, each through homogeneous stands of vegetation and together representing all riparian habitat types occurring in the area, were censused three times monthly for 2 yr (1977, 1978) to provide distributional records for all species. From the census data we divided the transects into three groups for each bird species each season: transects where the species was recorded in both 1977 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 48 publications
(61 reference statements)
3
35
0
2
Order By: Relevance
“…More important, perhaps, is the increasing number of studies that demonstrate at a local population level a strong association between individual bird species and one or more individual plant species (e.g., Snow and Snow 1971 ;Smith 1977;Holmes etal. 1979;Holmes and Robinson 1981;Maurer and Whitmore 1981 ;Wiens and Rotenberry 1981 ;Rice et al 1983;Robinson and Holmes 1984). Indeed, most avian ecologists are familiar with similar specific associations from their own field experiences.…”
Section: Discussionmentioning
confidence: 99%
“…More important, perhaps, is the increasing number of studies that demonstrate at a local population level a strong association between individual bird species and one or more individual plant species (e.g., Snow and Snow 1971 ;Smith 1977;Holmes etal. 1979;Holmes and Robinson 1981;Maurer and Whitmore 1981 ;Wiens and Rotenberry 1981 ;Rice et al 1983;Robinson and Holmes 1984). Indeed, most avian ecologists are familiar with similar specific associations from their own field experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Most ecological studies have used a descriptive approach (see, however, Rice et al 1983 andVerner et al 1986 for applications of predictive methods). The structure of the canonical variates is often of primary concern to ecologists.…”
Section: Munro and Rounds 1985 Seagle 1985)mentioning
confidence: 99%
“…Different species, each with unique habitat and food requirements and differing ability to migrate, respond accordingly. Studies in arid areas outside Australia have also shown that species vary greatly in abundance from year to year and place to place, apparently to some degree independently of each other Rotenberry 1980, 1981;Rosenberg et al 1982;Rice et al 1983aRice et al , 1983b.…”
Section: Discussionmentioning
confidence: 99%